VALUE-BASED EDUCATION MODEL TO BUILD STUDENTS OF INCLUSIVE ELEMENTARY SCHOOL’S CHARACTER - Mumpuniarti, Mumpuniarti; Fathurrohman, Fathurrohman; Sukinah, Sukinah (Dewantara, 2014)
This research is aimed at developing value learning model to build students? character in elementary schools that conduct inclusion model. This research used R & D (Research & Development) approach and was conducted in two stages. The first stage was a base line study to find out what was needed in value education in schools that conduct inclusive education (need assessment). Based on the assessment, a module was then drafted. After that, the draft was examined regarding its feasibility through a focused-group discussion and a small-scale tryout to an elementary school that conduct inclusive education. The result of this stage was a module draft which was used as a value learning model through story-telling and games. This model was set within seven (7) themes and was integrated to subjects taught in the elementary schools that conduct inclusive education.